Crack prediction of plastic housing subjected to impact loading - Teo, Chung Kiat (2008)
This report establishes a procedure or methodology to model and predict potential plastic crack on plastic housing at impact. A test rig is designed and fabricated to deliver tensile impact load to plastic tensile bar specimens and the final displacement on the plastic specimens at fracture are obtained. These values are used in the finite element analysis (FEA) simulation to establish thresholds to predict failure of product housing when impact loaded. Various notch sizes are introduced on the tensile specimens to study the effect of notch-induced crack. Similarly, the fracture displacements are also used in the FE modelling to obtain threshold. Dynatup drop dart test is also employed to study cracks on a multi-axial stress state.